A nanoparticle-based tour de force for enhancing immunogenic cell death elicited by photodynamic therapy. (31st December 2022) - Kepp, Oliver; Kroemer, Guido
ABSTRACT: Immunogenic cell death (ICD) involves the release of ATP, which can be destroyed by ectonucleotidases, converting it into immunosuppressive adenosine. Hence, inhibition of such ectonucleotidases is a strategy for enhancing ICD-elicited anticancer immunity. In a recent paper in Science Translational Medicine, Mao et al. report the construction of reactive oxygen-labile nanoparticles that bear two functionalities, namely (i) the capacity to sensitize cancer cells to near-infrared light (NIL) irradiation, hence inducing ICD in the context of photodynamic therapy, and (ii) the peculiarity to respond to NIL by releasing a pharmacological inhibitor of ectonucleotidases, hence enhancing intratumoral concentrations of ATP. In preclinical models, these nanoparticles are highly efficient in inducing anticancer immune responses.